Effects of Ion Characteristics on the Leaching of Weathered Crust Elution-Deposited Rare Earth Ore - Zhang, Zhenyue; Chi, Ru'an; Chen, Zhuo; Chen, Wendou (Frontiers in Chemistry, 2020)
To reveal the ion-exchange mechanism in the leaching process of weathered crust elution-deposited rare earth ores with different leaching agents, the variety of cations and anions were investigated in different concentration on leaching process, including Al^(3+), Fe^(3+), Ca^(2+), Mg^(2+), Na^+, K^+,〖 NH〗_4^+ and Cl^-, NO_3^-, SO_4^(2-). Meanwhile, the relation between different concentration of cations and anions and leaching efficiency were investigated, as well as the relation between different concentration of cations and anions and zeta potential were investigated. And the different ions on the swelling of clay minerals during leaching were also investigated. The results shown that 〖 NH〗_4^+ was the most affected electrolyte cations on rare earth leaching efficiency in the leaching process of weathered crust elution-deposited rare earth ore among three different cationic valence states, and the leaching efficiency was 86.93% at the optimal leaching concentration. The influence of the three anions on the leaching efficiency of rare earth was NO_3^->Cl^->SO_4^(2-), the leaching efficiency of rare earth were 83.21%, 81.52% and 80.12% at the optimal leaching concentration, respectively. The〖 NH〗_4^+ had the greatest effect on zeta potential of weathered crust elution-deposited rare earth ore, and the zeta potential was -18.1mV at the optimal leaching concentration. And the order of the effect of three anions on zeta potential was 〖SO_4^(2-)>NO〗_3^->Cl^-. Combined with the effect on the rare earth leaching process, anions and cations were considered separately and 〖 NH〗_4^+ and Cl^- were selected, the relation between the rare earth leaching efficiency and zeta potential conforms to the follow equations: 〖 NH〗_4^+:Y= -0.48X2-13.51X-1.58, R2=0.98133 and Cl^-:Y= -1.22X2-17.64X+23.29, R2=0.99010. And it was found in the swelling experiment of the weathered crust elution-deposited rare earth ore that the swelling ratio of clay minerals was the lowest when the cation and anion were 〖 NH〗_4^+ and Cl^-, and the swelling ratio were 1.874% and 2.015%, respectively.